Sodium Butyrate Modulates Mucosal Inflammation Injury Mediated by GPR41/43 in the Cecum of Goats Fed a High Concentration Diet - Chang, Guangjun; Ma, Nana; Zhang, Huanmin; Wang, Yan; Huang, Jie; Liu, Jing; Dai, Hongyu; Shen, Xiangzhen (Frontiers in Physiology, 2019)
Short chain fatty acids (SCFAs) are derived from microbial fermentation in the digestive tract and are detected by GPR41/43(G-protein coupled receptor 41/43) receptors belonging to the G-protein receptor family. Emerging data indicate that excessive SCFAs can mediate the downstream MAPK (mitogen-activated protein kinase) pathways by activating GPR41/43 to initiate the inflammatory response. The current study was conducted to investigate if a high concentrate (HC) supplemented with sodium butyrate can alleviate the inflammation and if an epigenetic mechanism is involved in regulating the expression of the key GPR41/43 genes in the cecum. Twelve lactating goats were divided into 2 groups: the control group fed the HC diet and the treatment group fed the HC diet supplemented with sodium butyrate (HCB). Our results suggested that the supplementation of sodium butyrate significantly increased the pH value in the rumen and cecum, downregulated the expression of GPR41/43 and related inflammatory cytokines, upregulated the expression of tight junction proteins, and reduced the protein expression levels of GPR 41/43, ERK1/2 and p38 in the goats in the HCB group compared with those in the HC group. Moreover, the ratios of DNA methylation and chromatin compaction in the promoter region of the GPR41/43 genes were altered due to the addition of sodium butyrate. In brief, dietary addition of sodium butyrate can reduce the inflammatory injury to the cecal mucosa in lactating goats and can affect the expression of GPR41/43 via epigenetic modification.